Europejskie podejścia do budowania wielowymiarowych kart dokonań przedsiębiorstwa - Nita, Bartłomiej (European Approach to Creation Multidimentional Corporate Scorecards, 2007)
The paper presents three basic European scorecards, which can be treated as alternative solutions towards Balanced Scorecard originally proposed by R.S. Kaplan and O.P. Norton. Namely, French Tableau de Bord, German version of corporate scorecard and Swedish Skandia Navigator were depicted and critically evaluated, taking into account five criteria.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 274-284